Palma Forrageira (Nopalea cochenillifera ( Salm Dyck)) na alimentação de ovinos em confinamento. - Lima, Talma Jordana (2018)
The objective was to evaluate nutrient intake and digestibility, productive performance, ruminal parameters, carcass characteristics, in vivo and carcass measurements, and non-carcass constituents, physical-chemical and sensorial quality of the meat. A total of 40 uncastrated male lambs with initial weight of 23.69 ± 3.08 kg were used in a completely randomized design with four treatments (0, 15, 30 and 45% spineless cactus inclusion) and ten replications, submitted to confinement system. The inclusion of increasing levels of Spineless cactus reduced the consumption of neutral detergent fiber (NDF), ethereal extract consumption and water consumption, however, increased the consumption of non-fibrous carbohydrates, as well as increased dry matter digestibility, organic matter and total carbohydrates, but decreased the digestibility of the NDF, however, does not compromise the performance. The time of eating and ruminating reduced and the leisure time increased, increasing the efficiency of dry matter intake (DM) and reduced ruminating efficiency of DM. There was a reduction in the efficiency of rumination of NDF at the level of 45%. Triglycerides and glucose increased, while cholesterol decreased at the 15% inclusion level. The inclusion of spineless cactus provided a reduction in feed costs and increased profits. The spineless cactus did not affect the NH3, however, it reduced the ruminal pH and increased the microbial protein, provided a reduction in the height of the papillae and the muscular layer of the rumen, and in the intestine provided increased mucosal height. Of the carcass characteristics only the weight of the empty body presented orthogonal contrast. The cold half carcass weights and the neck, palette and leg cuts showed a quadratic effect. There was no effect for non-carcass components and biometric measurements (MB). MB presented positive correlations with body weight at slaughter and carcass characteristics. Among the physico-chemical and sensory components of the meat, only the gray variables and the protein presented significant differences. In the analysis of main components, two components explained 84.46% of the total variability of meat quality characteristics. The inclusion of up to 30% fodder spineless cactus in the diets of lambs without defined breed improves the digestibility of the diet providing similar performances, without causing major alterations in the characteristics of the constituents and not constituents of carcass; in the physical-chemical and sensorial characteristics of the meat.